Testing and validation of travelling wave based fault detection and location method for offshore wind farm applications - Sujay Ghosh; Guangya Yang; Asmus G. Moser; Seyed A.H. Anaraki (Energy Reports, 2023)
This work investigates the efficiency of Travelling Wave (TW) based fault detection and locationing for multi-sectional cross-bonded export cable for offshore wind farm applications. The cables, instrument transformers and the offshore wind farm are modelled according to the TW method and practical conditions. In order to correctly reflect the offshore collection grid dynamics, an aggregation method that preserves the frequency response of the wind farm impedance is implemented. The result of the EMT simulation of the developed offshore system model is played back on an actual TW relay to test the reliability of the current-based TW FDL method. A simulation of TW FDL using wavelet transform is performed to verify the relay response. Through cross-validation with the relay testing result, the paper provides another aspect of the applicability of TW relay for offshore applications.